Pengendalian Bencana Alam: Efektivitas Mitigasi Banjir di Kabupaten Kudus - Muh Rafi Alfaris; M. Nur, Dany Miftah (Jurnal Riset Sosial Humaniora dan Pendidikan, 2025)
Flooding is a disaster that comes from nature directly, whether it is caused by the frequency of high rainfall or the capacity of rivers that are unable to stem the swift flow of water. Thus, appropriate measures (Mitigation) are needed to be able to cope with flood natural disasters. This research intends to conduct an in-depth field study related to flood disasters in Kudus Regency and its mitigation guidelines. Then the researcher evaluates whether the mitigation measures can have a significant impact on the decline of flood natural disasters in Kudus Regency. The research method in this study applies qualitative with a field study approach style. Based on the previous research, it was found that several measures have been taken to mitigate the occurrence of flood disasters. However, these steps have in fact not been able to overcome flooding in Kudus Regency. Based on the results of an in-depth analytical study by applying the theory of policy effectiveness by Joseph John Campbell, it was found that several flood disaster mitigation efforts carried out by the Kudus Regency Government were still ineffective because they had not been able to significantly reduce the incidence of flooding. Policy improvements and more assertive program implementation are needed so that the results are more optimal.